Evaluating the efficiency of using ChatGPT and Google Services for scientific search - Манько, Д.Ю.; Беляк , Є.В.; Крючин , А.А.; Євтушевська , О.В. (Інститут проблем реєстрації інформації НАН України, 2024)
This research is devoted to comparison of ChatGPT and Google Search Engine in information retrieval efficiency, accuracy, and user experience. Through experiments and user studies, the study assesses their performance in various tasks, including question answering and dialogue interactions. Key metrics like response time, result relevance, query comprehension, and user satisfaction are compared, highlighting the strengths and weaknesses of each system. ChatGPT stands out in natural language understanding and personalized interactions, whereas Google Search Engine excels in quickly retrieving vast web information accurately. The findings offer insights into AI-driven conversational agents and traditional search engines, guiding the development of better information retrieval systems and enhancing online user experiences.